David Gorton: variations on John Dowland - Gorton, David; Skaerved, Peter Sheppard; Östersjö, Stefan (London TOCCATA CLASSICS, 2017)
John Dowlands pavan Lachrimae was one of the hits of the early 1600s: musicians all over Europe made their own versions of it. The English composer David Gorton (b. 1978) proves that Dowlands fascination endures, with this album of music that has its points of departure in Dowland, linking his time and ours over a span of 400 years with a dig at some contemporary politicians along the way.